Expression profiling of circulating miRNAs in mouse serum in response to Echinococcus multilocularis infection. Issue 8 (8th March 2017) - GUO, XIAOLA; ZHENG, YADONG
SUMMARY: Echinococcus multilocularis is a most pathogenic zoonotic tapeworm that causes devastating echinococcosis in both humans and animals. Circulating microRNAs (miRNAs) are stably existed in the serum/plasma of mammalian hosts during helminthic infection. In this study, we compared the host-circulating miRNA expression in the sera from the E. multilocularis -infected and uninfected mice. A total of 58 host-origin serum miRNAs were differentially expressed (2 ⩾ fold change, P < 0·05), of which 21 were upregulated and 37 were significantly downregulated. Consistent with the sequencing data, quantitative polymerase chain reaction (PCR) results showed that the expression levels of four miRNAs were elevated gradually and one decreased gradually at the E. multilocularis infection time points. Moreover, seven of E. multilocularis specific miRNAs were identified in the sera. Real-time PCR analyses further demonstrated that only two parasite-derived miRNAs (emu-miR-10 and emu-miR-227) were specifically amplified in all the sera from mice infected with E. multilocularis . These findings will be helpful to understand the roles of miRNAs in host–parasite interaction and to potentiate serum miRNAs as diagnostic targets for echinococcosis.